Marmota caligata - Robert S. Hoffmann; Charles G. Anderson (Smithsonian Institution Press, 1993)
Marmota caligata (Eschscholtz, 1829). Zool. Atlas, Part 2, p. 1, pl. 6. TYPE LOCALITY: Not specified (?). Restricted by Allen (1877:927) to near Bristol Bay, Alaska, USA. DISTRIBUTION: C Alaska (USA), Yukon and Northwest Territories (Canada) south to W and NE Washington, C Idaho, and W Montana (USA). SYNONYMS: cascadensis A. Howell, 1914; nivaria A. Howell, 1914; okanagana (King, 1836); oxytona Hollister, 1914; raceyi Anderson, 1932; sheldoni A. Howell, 1914; sibila Hollister, 1912; vigilis Heller, 1909. Published as part of Robert S. Hoffmann & Charles G. Anderson, 1993, Order Rodentia - Family Sciuridae, pp. 419-465 in Mammal Species of the World (2 nd Edition), Washington and London :Smithsonian Institution Press on page 431, DOI: 10.5281/zenodo.7353130